Study of the TEAD‐binding domain of the YAP protein from animal species. (20th November 2020) - Mesrouze, Yannick; Bokhovchuk, Fedir; Meyerhofer, Marco; Zimmermann, Catherine; Fontana, Patrizia; Erdmann, Dirk; Chène, Patrick
Abstract: The Hippo signaling pathway, which plays a central role in the control of organ size in animals, is well conserved in metazoans. The most downstream elements of this pathway are the TEAD transcription factors that are regulated by their association with the transcriptional coactivator YAP. Therefore, the creation of the binding interface that ensures the formation of the YAP:TEAD complex is a critical molecular recognition event essential for the development/survival of many living organisms. In this report, using the available structural information on the YAP:TEAD complex, we study the TEAD‐binding domain of YAP from different animal species. This analysis of more than 400 amino acid sequences reveals that the residues from YAP involved in the formation of the two main contact regions with TEAD are very well conserved. Therefore, the binding interface between YAP and TEAD, as found in humans, probably appeared at an early evolutionary stage in metazoans. We find that, in contrast to most other animal species, several Actinopterygii species possess YAP variants with a different TEAD‐binding domain. However, these variants bind to TEAD with a similar affinity. Our studies show that the protein identified as a YAP homolog in Caenorhabditis elegans does not contain the TEAD‐binding domain found in YAP of other metazoans. Finally, we do not identify in non‐metazoan species, amino acid sequences containing both a TEAD‐binding domain, as in metazoan YAP, and WW domain(s).